EXPERIMENTAL RESEARCH ON DIAMOND WHEEL DRESSING BASED ON DYNAMIC MODEL - CHI YuLun; TAN ShaoDong; GU JiaJian (Jixie qiangdu)
To reduce the vibration of the diamond roller shaft during the dressing process through the experimental study of the diamond roller dressing process to improve the grinding wheel morphology and subsequent grinding surface quality. Firstly, the vibration mechanism of diamond wheel dressing is described, and the dynamic characteristics of dressing device have important influence on dressing process and subsequent grinding. Then diamond roller dressing dynamics model is established and the model is divided into two parts of the grinding wheel and diamond wheel, and by changing the diamond roller shaft support materials to change the contact stiffness, damping, and stiffness and numerical simulation calculation, analysis of diamond roller shaft in the use of steel support material and casting the vibration of the support material circumstances difference; Finally, through experimental verification, it shows that the surface quality of the subsequent grinding workpiece is different in the case that the vibration of the diamond roller shaft is larger and smaller. The numerical value of the vibration amplitude of the diamond roller shaft supported by the steel material was 1.5×10-6m/s~2, and the maximum value of the vibration amplitude of the casting material support was about 0.3×10-6m/s~2. The diamond roller shafts with supporting materials of steel and casting are used for dressing, and then grinding is performed. The surface of the workpiece ground by the former has burns, while the surface of the latter is qualified. The dynamic characteristics of dressing device have a great influence on the vibration during dressing. When other conditions remain unchanged, the greater the stiffness, damping and contact stiffness, the more stable the dressing process will be. The larger the vibration during the dressing process, the worse the surface morphology of the dressed grinding wheel, and the more likely the workpiece will be burned during grinding.